Towards shorter immaturity and improved yields by mulching with rice straw - Samarappuli, L.; Yogaratnam, N.; Samarappuli, P.; Mitrasena, U. (Rubber Research Institute. Agalawatta, 1992)
In this study with immature Hevea brasiliensis, multing with paady straw around the base of the tree was found to be a better agronomic practice than growing leguminous cover crops such as Pueraria phaseoloides and Desmodium ovalifolium or allowing natural vegetation to grow in the inter-row area. Girthing had been much higher with mulching which resulted into reduction of the immature, unproductive period by approximately 18 and 12 month in comparison with naturals and creeping legumes respectively. In addition to early tapping, yield of latex was also higher during the early stages, increases in the region of 33perc. and 40perc. in comparison with creeping legumes and naturals respectively. The present value of the benefit achieved from mulching amount to Rs. 31,088/= per hectare of which Rs. 19,740/= is due to extra yield and the balance of Rs. 11,348/= is saving on inputs as a result of early maturity. Consequently, a net present value (NPV) of Rs. 7.8 million at national level can be achieved with the above practice at 50perc. level of adoption
Keywords: Agriculture; Rubber; Soil management; Plant growth; Yield; Soil fertility